Reforming External Tariffs in Central and Western African Countries - Doe, Lubin Kobla (IMF Working Papers; Working Paper, 2006)
This paper examines the reform of the external tariff initiated by the CEMAC and the WAEMU that is aimed at reinforcing their economic integration. Overall, there is broad compliance with the streamlined and moderate rates, but with significant deviations from the harmonized paths in several countries. WAMZ countries, except Ghana, need to undertake major reforms in order to align their external tariff structures with that of the WAEMU as planned for 2007. To promote full compliance with the harmonized external tariff policies, the paper suggests, measures need to be taken, including the creation of financial incentives, at the regional and country levels.